(untitled) (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
This case discussion focuses on the judicial function of the African Court on Human and Peoples’ Rights (Court) in default judgments. The discussion brings to the foreground the changes introduced by the Court in its recently revised Rules of Procedure and how these changes are put in practice in its case law. The revised provision on default judgments includesthe extended power of the Court to decide on its own motion on whether to issue a default judgment and the introduction of a legal innovation in international dispute settlement, namely, a remedy for the defaulting party to set aside a default judgment. The recent default judgment in Léon Mugesera v Rwanda serves as a focal point in the analysis since it is the first instance that the revised Rules of Procedure were put into practice and since the Mugesera case illustrates the difficulties encountered by the Court in cases of non-appearance of the respondent state. The Court’s Rules of Procedure and case law are also placed within the corpus of international (human rights) law and the jurisprudence of its two regional counterparts on matters pertaining to default judgments so as to shed light on different approaches. The analysis makes two main arguments. The first concerns theprocedural requirements for rendering a judgment in default. Until the Mugesera decision, the Court was not consistent in meeting these requirements, and had been known to decide in default on its own motion without having a textual basis in the Protocol or the Rules of Procedure to do so. The recently revised Rule of Procedure grants the Court the power to decide on its own motion. Second, the analysis argues that the Mugesera decision cements an alarming trend in the case law, whereby in cases of nonappearance the Court does not satisfy itself that the applicant’s submissions are well-founded.